Qualidade física de um latossolo vermelho sob diferentes coberturas em áreas de restauração do PNMCBio, Sorocaba/SP - Scaglianti, César Augusto da Costa (Universidade Federal de São Carlos, 2022)
For the soil to perform well its functions, it is necessary that his indicators stay within certain boundaries to performance well, regulate processes properly that depends on good water drainage and storing, air circulation and his structural functionality, necessary conditions for root growing, and give support to the plants. In another way, it must be recognized that soil functionalities, as well as its processes perform depends on the vegetal coverage kind and the associated management employed. This understanding is even more important in degraded areas which are passing through voluntary restoration process, where the lack of metrics and indicators, mainly for soil and water represent a challenge for researchers and protect areas managers. The goal of this research was to verify the impact that forest coverage has over physics and hydrological attributes in a Latossolo Vermelho (Oxisols), located at Parque Municipal Natural Corredores da Biodiversidade, a protected area in Sorocaba municipality. The research was conducted in a semideciduos forest in early secondary stage established in a meadow (VH), a semideciduos forest in early secondary stage established in a former eucalyptus commercial forest (ECP), a semideciduos forest in early secondary stage establish in a soil disposal area (BF), and a semideciduos forest in middle secondary stage (MTA). In each area it was aleatory set 03 parcels with 9 m2 which samples and field prospective essays in situ were carry out in 0 a 0,20 m e 0,20 a 0,40 m layers. The investigated attributes were composed by indicators (characteristics or properties) physical, hydrological and mechanical that are inherent to the soil as texture, and other properties that are dynamic and change in a shorter time scale according to disturbances caused by weather, soil management and vegetation considered in this study. Among the indicators there are those that are determinants of soil functioning: a) mass and volume relation soil constituents; b) soil structural stability; c) hydrological dynamics; d) soil organic matter. The research outputs show how strategic it is to define, study and investigate the physical-hydrological-mechanical soil attributes, relating them to soil chemical quality in order to figure out the impact of forest vegetation over soil structural functions in forest restoration areas. It is also possible to conclude that soil organic matter (SOM), has a positive impact over the soil structural functionality, although the indicators used in this research show, with the exception of MTA, the restoration strategies used to recover PNMCBio forest areas didn’t produce the improvement expected for the forest restoration or ecological forest process, regarding physical-structural quality of the Latossolo Vermelho.
Soil physical quality of a latossolo vermelho (oxisol) under differents vegetal coverages in restoration areas of the PNMCBio, Sorocaba/SP
Keywords: Atributos físicos do solo; Restauração florestal; Qualidade do solo; Soil physical atributes; Forest restoration; Soil Quality; Áreas degradadas; Degraded areas; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FISICA DO SOLO; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS